Movement 2 (?) of "The Dance" based on Beethoven's Seventh Symphony - Bothwell, Dorr Hodgson, 1902-2000 (artist):::Creator:::::::::::: (2021)
One of four paintings, gouache on paper, each depicting one movement of Beethoven's Seventh Symphony, op. 92.